Merayakan Living Heritage Batik Rifaiyah: Sebuah Tafsir atas Undang-Undang Pemajuan Kebudayaan - Mochammad Najmul Afad (Universitas Andalas, 2023)
This paper describes the emphasis on rifaiyah batik which is a characteristic of rifaiyah people who are trying to be distracted by cultural activities through an activity entitled Celebrating Rifaiyah Batik which is seen in terms of interpretation of the Law on the Promotion of Culture. This research uses ethnographic methods and studies on Law Number 5 of 2017 concerning the Pemajuan Kebudayaan. The results showed that rifaiyah batik was made by rifaiyah people living in the Batang region. Rifaiyah batik is not just batik, but becomes a daily activity as well as a spritual practice of the rifaiyah. An activity entitled Celebrating Rifaiyah Batik was held as a form of concern, preservation and advocacy for rifaiyah batik to be known by the wider community by bringing the core message of rifaiyah batik. This is so if contextualized by Law Number 5 of 2017 concerning Pemajuan Kebudayaan, it becomes complete that the community as the owner and driver of culture. This research recommends that the interpretation of Law Number 5 of 2017 concerning the Promotion of Culture be interpreted transformatively. The government as a policymaker should support and create an atmosphere so that the community always preserves culture by continuing to explore the values of locality that exist in the context of promoting culture itself, regional development both in the human resources sector, economy and other sectors with cultural roots.